Integrated omics identifies molecular networks of brain-body interactions of brain injury - Yuan-Hong Deng; Hong Wang; Jia-Hang Zhang; Yu-Fei Wang; Meng-Yao Wang; Xin-Ru Pan; Yao-Dan Zhang; Yuan-Hui Gan; Yi He; Fang Xie; Xiao-Shuang Feng; Jia-Xin Xie; et al. (iScience)
Summary: The molecular mechanisms of brain-body interactions in the progression of brain diseases remain unknown. Through integrative analysis of multi-organ proteomic, metabolomic, and transcriptomic data following ischemic stroke, we identified dynamic molecular signatures across organs. The heart exhibited the highest number of differentially expressed proteins (DEPs), followed by spleen and intestine. Ten DEPs were shared among three organs post-stroke, with eight in heart, six in spleen, and five in intestine. Notably, organs displayed accelerated biological aging, particularly the intestine, ‌which is implicated in neurobehavioral regulation. Conjoint analysis further confirmed that DEPs originated from both intrinsic and immune cells that systemically infiltrated multiple organs. Finally, plasma DEPs showed high correlations with corresponding protein levels in distinct organs, potentially resulting in the systemic circulation of stroke. Our findings provide a comprehensive atlas of stroke-induced multi-organ molecular remodeling and establish a foundational framework for developing systemic therapeutic strategies targeting brain-body interactions in brain injury.